Sustaining ethnic identity through fashion / Jenefer Masirin and Prinses Saliang - Masirin, Jenefer; Saliang, Prinses (Universiti Teknologi MARA, 2018)
This study focuses on implementing the Kadazan Dusun ethnic identity into modern fashion. In the recent years, the local designers had been striving to the challenge of creating a contemporary representing the Kadazan Dusun, with the Unduk Ngadau as the main platform to showcase their creation. With this new category added to the competition, modern fashion has clearly made its way into the traditional event. This study will be conducted through qualitative research methodology, by interviews and observation with the people who are directly and indirectly involved in the competition. This study will give a proper suggestion and recommendation on how the modern fashion can be used as a medium in sustaining the Kadazan Dusun identity.